The leukemia-lymphoma cell line factsbook - Drexler, Hans G. (Factsbook series., 2000)
This book represents an essential reference manual for all of the well-characterized leukemia-lymphoma cell lines currently available. It provides the most important facts, using the succinct and user-friendly format that has made the FactsBooks so popular with scientists and clinical researchers. Introductory chapters provide background and perspective for culturing malignant hematopoietic (blood forming) cell lines. These chapters are followed by over 400 comprehensive individual entries. Each cell line entry highlights essential clinical, immunological, genetic, and functional features and includes a comprehensive listing of references. Key Features * the full spectrum of malignant cell lines from all hematopoietic cell lineages * sister cell lines and relevant subclones * clinical data: patient, diagnosis, treatment status, and specimen source * authentication of derivation and availability * immunophenotype * cytogenetic karyotype * translocations and fusion genes * receptor gene rearrangements and genetic alterations * cell cultures aspects: establishment, medium, doubling time, growth * cytochemical profile * cytokine production and response to cytokines * proto-oncogene and transcription factor expression/alteration * functional features: differentiation induction, heterotransplantability * special unique features * key references.